Cambios morfológicos del cálamo de las plumas remeras en crecimiento de palomas - Martínez Calles, María del Rosario; Garrido Fariña, Germán Isauro; González Díaz, Francisco Rodolfo; Nieto Bordes, José Luis; Juárez Mosqueda, María de Lourdes; Soto Zárate, Carlos Ignacio; Higuera Piedrahita, Rosa Isabel; García Tovar, Carlos Gerardo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 15-24).